The effect of pentoxifylline on oxidative stress in chronic kidney disease patients with erythropoiesis-stimulating agent hyporesponsiveness: Sub-study of the HERO trial. (2nd January 2016) - Zhang, Lei; Coombes, Jeff; Pascoe, Elaine M.; Badve, Sunil V.; Dalziel, Kim; Cass, Alan; Clarke, Philip; Ferrari, Paolo; McDonald, Stephen P.; Morrish, Alicia T.; Pedagogos, Eugenie; Perkovic, Vlado; et al.
Abstract : Objective : Pentoxifylline has previously been shown to increase haemoglobin levels in patients with chronic kidney disease (CKD) and erythropoietin-stimulating agent (ESA)-hyporesponsive anaemia in the HERO multi-centre double-blind, randomized controlled trial. The present study evaluated the effects of pentoxifylline on oxidative stress in ESA-hyporesponsive CKD patients. Methods : This sub-study of the HERO trial compared 15 patients in the pentoxifylline arm (400 mg daily) and 17 in the matched placebo arm on oxidative stress markers: plasma total F2-isoprostanes, protein carbonyls, glutathione peroxidase (GPX), and superoxide dismutase (SOD) activities. Results : Pentoxifylline did not significantly alter total F2-isoprostanes (adjusted mean difference (MD) 35.01 pg/ml, P = 0.11), SOD activity (MD 0.82 U/ml, P = 0.07), GPX activity (MD −6.06 U/l, P = 0.09), or protein carbonyls (MD −0.04 nmol/mg, P = 0.52). Replicating results from the main study, pentoxifylline significantly increased haemoglobin concentration compared with controls (MD 7.2 g/l, P = 0.04). Conclusions : Pentoxifylline did not alter oxidative stress biomarkers, suggesting that alternative mechanisms may be responsible for the agent's ability to augment haemoglobin levels in CKD patients with ESA-hyporesponsive anaemia.